معاصرمسائل میں سےعدالتی خلع کی شرعی حیثیت،تجزیاتی مطالعہ: Disclosing the Contemporary issues: An Analytical Exploration of the Shariah Status in Judicial Khula - Inam Uddin; Shamsher Ali; Dr. Syed Toqeer Abbas (Al Manhal Research Journal, 2023)
The fundamental of Islamic system is to strengthen and stabilize the family system. This is the reason why Islam has given an extra ordinary importance to this relation and advised the spouse to behave with love and compassion with each other, because marital system is the beginning of the family system. If the unity of the family is strong and reliable then the coming generations will be strong and enduring. This is the reason why Allah Almighty called husband and wife clothing for each other, wife is for husband and husband is for wife. But if there is an any rift or turmoil in marital life and the situation get as worse as that there is no way out to mend this relationship anymore, then Islam allowed/permitted Khula or Divorce in spite of its notoriety. If the wife disobedient and rebellious towards her husband, then the husband have the right to separate from the wife by giving divorce. And if the husband is cruel and abusiveness towards the wife and he is unable give basic rights and basic needs to the wife, then the wife has the legal right to live separately, while returning all the marital gifts to the husband, and that is called Khula. But if the Khula is demanded by wife and the husband is not agreed to give Khula, and the wife has no desire to live anymore with husband, in such situations mostly the wife has to go to court and get the certificate of Khula. In Pakistani courts, such decisions are always illegal in all three jurists except Imam Malik because according to them, the wife cannot get out of the marriage contract through "khula" unless the consent of the husband is involved. Be However, in the case of Imam Malik and some contemporary scholars, the court is not bound to obtain the consent of the husband in this case. In this study we analyzed the consent of the husband in Khula while taking into account the concept of Holy Qur’an, the traditions of Holy Prophet PBUH and the opinions and decisions of the companions.